(untitled) (Journal of Economic Research & Business Administration, 2020)
The importance of collaboration between universities and business (UBC) continues to grow in all countries. The reasons for this are numerous, such as changes in innovation structures, the development of the knowledge society, and national and international higher education policies. Kazakhstan, as a rapidly developing country, is experiencing all these changes. Nowadays, activities of university are evolving from the basic functions of teaching and research to commercialisation of research results where the partnership with the private sector is one of the most important elements. The purpose of the article is to identify influencing factors, driving factors and barriers for UBC, as well as recommendations for the future. The data for analysis was obtained using an online survey. The survey was conducted among University employees and company employees. More than 100 respondents took part in the survey. The results of the survey show that the main factors influencing the cooperation of universities and business: sources of funding, innovative indicators of universities, the impact of funding sources on control mechanisms and innovative activities of universities, also, the likely reason for the lag is the slow and still incomplete transition of Kazakhstan from the “traditional” innovation system to the modern innovation ecosystem.